2010
DOI: 10.1186/1472-684x-9-15
|View full text |Cite
|
Sign up to set email alerts
|

Morphinofobia: the situation among the general population and health care professionals in North-Eastern Portugal

Abstract: BackgroundMorphinofobia among the general population (GP) and among health care professionals (HP) is not without danger for the patients: it may lead to the inappropriate management of debilitating pain. The aim of our study was to explore among GP and HP the representation and attitudes concerning the use of morphine in health care.MethodsA cross-sectional study was done among 412 HP (physicians and nurses) of the 4 hospitals and 10 community health centers of Beira Interior (Portugal)and among 193 persons o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 44 publications
3
33
1
Order By: Relevance
“…Among the results obtained, it is noteworthy that most respondents did not have a clear idea about opioids and those who did mostly considered them to be related with pain, illegal drugs, and medication. This is consistent with the findings of a study carried out in Portugal, 13 where 32.3% of the general population were unable to recognize the term morphine. However, when these individuals were specifically asked about this drug, 99.2% answered that they knew about it although it was only identified as an opioid by 64.9% of them.…”
Section: Discussionsupporting
confidence: 92%
“…Among the results obtained, it is noteworthy that most respondents did not have a clear idea about opioids and those who did mostly considered them to be related with pain, illegal drugs, and medication. This is consistent with the findings of a study carried out in Portugal, 13 where 32.3% of the general population were unable to recognize the term morphine. However, when these individuals were specifically asked about this drug, 99.2% answered that they knew about it although it was only identified as an opioid by 64.9% of them.…”
Section: Discussionsupporting
confidence: 92%
“…65,66 Although there are many effective pharmacological and non-pharmacologic pain treatments available, 67 opioids are essential for management of MSCP. 39 Opioid analgesics have been regarded as the bastion of surgery and trauma related pain treatment for many years, 36 national encouragement of their use for CRP did not occur until roughly ten years ago.…”
Section: Resultsmentioning
confidence: 99%
“…6 That was implied in a crosssectional study aiming at exploring the significance and attitudes concerning the use of morphine, with 412 Portuguese participants (physicians and nurses) working at different settings (four hospitals and 10 community health centers). 11 It showed that 'morphine' firstly suggested 'analgesia' to only 32.9% of professionals. The reasons for Keywords: Analgesics, Opioid; Cancer Pain; Pain Management; Pain Measurement Palavras-chave: Analgésicos Opióides; Avaliação da Dor; Controlo da Dor; Dor Oncológica not using morphine were fear both of legal risks (56.3%) and of adverse side effects, such as somnolence-sedation (30.5%).…”
Section: Opioid Consumption In Portugalmentioning
confidence: 99%